Data hiding to the image with bit plane slicing and double XOR - Bilgi Özdemir; Nurettin Doğan (MANAS: Journal of Engineering)
Data hiding is done in different environments and with different techniques, and applications in this area attract a lot of attention. In data hiding, the method of securing the data in the image by hiding data is one of the steganography methods. Bit Plane Slicing, one of the techniques applied in image steganography, is a reliable technique applied on images such as data hiding or compression, which allows us to operate on some special bits by separating each pixel that makes up the image into planes. This technique is aimed to provide high image quality and data security. In this study, two encryption layers and a concealment stage are proposed. Here, the bit planes of the three channels of the color image were first extracted using the BPS technique. The message to be hidden later was encrypted using a double XOR operation using binary representation and a secret key (extracted from the MSB). Then, the stream of encrypted bits is hidden in the cover image using the least significant bit plane. Well-known evaluation criteria such as MSE, PSNR, and histogram distribution were calculated to ensure the quality of the proposed method. Experimental results show that the proposed method has acceptable results and maintains the security of confidential text messages.